Video, audio, and multimedia systems (Communication technology, 2004)
This program describes how video, audio and multimedia systems work. After recapping the history of TV, the video segment focuses on the basics of electronic communications, such as transmitters, receivers, channel frequencies and satellite transmitters, receivers, channel frequencies, and satellite transmission. Next, the audio segment examines the work of sound engineers, both in recording studios and at radio stations, and the equipment they use, including microphones, mixing consoles and recorders. Finally, the multimedia segment wraps things up with a look at virtual reality, the internet, CD-ROMs, and other elements of high-tech communications